Preparation and emission characteristics of ethanol-diesel fuel blends - Zhang, Run-Duo; He, Hong; Shi, Xiao-Yan; Zhang, Chang-Bin; He, Bang-Quan; Wang, Jian-Xin (Journal of environmental sciences (China), 2004)
The preparation of ethanol-diesel fuel blends and their emission characteristics were investigated. Results showed the absolute ethanol can dissolve in diesel fuel at an arbitrary ratio and a small quantity of water(0.2%) addition can lead to the phase separation of blends. An organic additive was synthesized and it can develop the ability of resistance to water and maintain the stability of ethanol-diesel-trace amounts of water system. The emission characteristics of 10%, 20%, and 30% ethanol-diesel fuel blends, with or without additives, were compared with those of diesel fuel in a direct injection (DI) diesel engine. The experimental results indicated that the blend of ethanol with diesel fuel significantly reduced the concentrations of smoke, hydrocarbon (HC), and carbon monoxide (CO) in exhaust gas. Using 20% ethanol-diesel fuel blend with the additive of 2% of the total volume, the optimum mixing ratio was achieved, at which the bench diesel engine testing showed a significant decrease in exhaust gas. Bosch smoke number was reduced by 55%, HC emission by 70%, and CO emission by 45%, at 13 kW/1540 r/min. However, ethanol-diesel fuel blends produced a few ppm acetaldehydes and more ethanol in exhaust gas.